US FOREIGN POLICY IN THE 21ST CENTURY AND THE QUESTION OF MORALITY IN INTERNATIONAL RELATIONS IN THEORY AND PRACTICE - Nikolic, Danijela; Talovic, Violeta (Serbian political thought, 2024)
The development of modern and powerful countries is conditioned by the need to possess and control significant amounts of resources. Out of the desire to increase the real power and influence of the global political plan, the great powers create conflicts, frictions and wars, neglecting the moral dimension and the negative consequences of the decisions taken. This paper aims to elaborate on the role of the great powers in triggering energy wars, focusing on the disguise of neo-imperial ambitions under the guise of fighting for human rights and democracy. With this in mind, the paper is divided into two parts. In the first part, the authors examine the phenomenon of war as well as the moral justification of wars by analyzing the ethical perspectives of war. In the second part, the authors’ attempts to explain how power and politics are put at the service of the ideological justification of decisions. The method of content analysis, the analysis of contemporary methods, and case studies are used as instruments to prove the hypotheses put forward. The author’s intention is to prove that energy and economic wars, which imply economic and political sanctions, are set in motion with the aim of destroying the economic potential of opposing economies and states that oppose certain geopolitical interests of the great powers. They turn the war for resources into a powerful weapon to assert their interests.